Cocoa agroforest multifunctionality and soil fertility explained by shade tree litter traits - Sauvadet, M.; Saj, S.; Freschet, G.T.; Essobo, J.D.; Enock, S.; Becquer, T.; Tixier, P.; Harmand, J.M. (Wiley, 2020)
Manipulating plant functional diversity to improve agroecosystem multifunctionality is a central challenge of agricultural systems world‐wide. In cocoa agroforestry systems (cAFS), shade trees are used to supply many services to farmers, yet their impact on soil functioning and cocoa yields is likely to vary substantially among tree species. Here we compared the impact of five shade tree species (Canarium schweinfurthii (Canarium), Dacryodes edulis (Safou), Milicia excelsa (Iroko), Ceiba pentandra (Kapok tree), Albizia adianthifolia (Albizia)) and unshaded conditions on the functioning of poor sandy savanna soils within eight cocoa farms in Central Cameroon. We assessed the effects of plant functional traits, leaf litterfall and fine root biomass on a range of soil functions and on cocoa yield. Synthesis and applications. We demonstrate that cocoa agroforest multifunctionality is substantially influenced by the functional traits of shade tree species. Shade tree species with the most dissimilar traits to cocoa (cocoa showing the lowest leaf litter quality) showed the largest improvement of soil functions. Therefore, selection of shade trees based on their functional traits appears as a promising practice to adequately manage soil functioning. In order to fully assess the beneficial role of shade trees in these agroecosystems. Future research will need to extend this approach to other below‐ground traits and other aspects of multifunctionality such as long‐term cocoa health and yield.